Chlorophyll fluorescence and leaf nutritional status of passion fruit (Passiflora edulis f. flavicarpa) seedlings grown in different organic substrates - Giler , Luís; Celi, Adriana; Cedeño, Galo; Cedeño-García, George (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
Passion fruit (Passiflora edulis f. flavicarpa) has high economic and nutritional value, and the nursery stage is crucial for its early development. The objective of the present study was to evaluate chlorophyll fluorescence, foliar nutritional status, and growth of passion fruit seedlings in response to four organic substrates: S1 (sand + biochar + organic matter), S2 (sand + compost + organic matter), S3 (sand + compost + agricultural soil), and S4 (agricultural soil), under a completely randomized design. The physiological variables Fv/Fm, Φ(II), and ETR were measured, as well as the foliar concentration of macro and micronutrients and growth variables, whose data were analyzed using ANOVA and Tukey's test (5%). Plants grown in substrate S2 showed the highest photochemical efficiency (Fv/Fm ≈ 0.79; Φ(II) ≈ 0.44; ETR ≈ 160), whereas those in substrate S1 exhibited the highest foliar concentrations of K, Fe, and Zn. The principal component analysis explained 71% of the total variability, associating substrate S2 with better physiological yield and growth. It can be concluded that substrates containing compost enhance PSII photochemical efficiency, while those including biochar are associated with greater foliar mineral accumulation.